Sawahlunto The Cultured City Mine Tour - Darista, Yulid; Dasrizal, Dasrizal; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
First coal mine in Sumatra is operated coal mine in Sawahlunto Ombilin in 1892 . But over time , the triumph of coal in Sawahlunto began a drastic decline since the early 2000s . Seeing the condition of depletion of coal since then Sawahlunto city government set its vision as